Characterization of the expected seismic damage for a critical infrastructure: the case of the oil pipeline in Friuli Venezia Giulia (NE Italy) - Tamaro, Alberto; Grimaz, Stefano; Santulin, Marco; Slejko, Dario (Bulletin of earthquake engineering, 2018)
Seismic codes using the performance-based approach for seismic design of critical and important structures generally refer to seismic hazard which takes into account a lower exceedance probability than that used for ordinary buildings. In the present study, the seismic hazard for an oil pipeline, located in the Friuli Venezia Giulia region (NE Italy), has been calculated in terms of PGA and PGV with a 2475-year return period, and compared with estimates calculated with the standard 475-year return period used for ordinary buildings. The results, referring to three soil types (rock, stiff soil, and soft soil), have been combined through GIS technology in a single map (soil seismic hazard map) on the basis of the local lithological characterization. The major earthquakes considered in the study have been associated with the linear sources found in the database of Italian seismic sources, considering the characteristic earthquake model. The regional seismogenic zonation has been added to the linear sources in order to consider minor seismicity as described by the Gutenberg–Richter model. Quaternary faults in the broader Trieste area, long enough to justify, at least, a characteristic magnitude of 6, have been added in the source model to take into account unlikely but possible unknown sources. The Transalpine Oil Pipeline, which connects Trieste (Italy) to Ingolstadt (Germany), is the crude-oil distribution system considered in the present study. It consists of a storage tank, compressor stations, and buried pipeline. For the characterization of the expected damage to the infrastructure in case of an earthquake, we have used underground pipeline seismic vulnerability curves that relate a performance indicator, such as the reparation rate (number of ruptures per kilometre), with a representative ground motion parameter (e.g., PGA or PGV). In this study, we have considered as performance indicator the consequences of a rupture in the pipeline caused by a seismic event.